SOME MORPHOFUNCTIONAL PARAMETERS OF HUMAN ADRENAL GLANDS IN THE FORENSIC DIAGNOSIS OF TRAUMATIC BRAIN INJURY - Sukhrob A. Rayimberdiev; Ibragim I. Bakhriev (Central Asian Journal of Medicine, 2023)
The article presents the results of a comparative study of the morphofunctional reaction of the human adrenal glands in cases of violent death caused by traumatic brain injury. The pathomorphological characteristics of the adrenal glands in people who died of a brain variant of thanatogenesis of people who died from mechanical trauma were compared. Morphological differences in the adrenal response were revealed. It is proposed to use the assessment of the morphofunctional state of the adrenal glands as additional forensic criteria for diagnosing death from traumatic brain injury.